Konsep Dasar dan Ruang Lingkup Manajemen Madrasah/Sekolah - Abidatul Chasanah Chasanah; Moh Irfannur Rasyid; Laila Badriyah (Program Studi Pendidikan Agama Islam UNU Purwokerto, 2024)
Abstract: The basic concept of Islamic educational leadership is an interesting topic that has received serious attention from teachers and educators. Teaching quality can be checked through educational management methods. This study discusses the notion of Islamic education administration, the principles of Islamic education administration, the basics of Islamic education administration, and the scope of Islamic education administration with the aim of understanding the basic concepts of administration. Islamic education requires the madrasah MBM system to independently research, distribute, prioritize key issues, monitor education, and be accountable for strengthening community and state resources. MBM is also a form of educational reform which provides special serving madrasas to provide better and proper education to students. It can also improve employee performance, enable direct stakeholder participation, and increase public understanding of the training. With regard to reforming madrasa administration, we cannot abandon the principles of general administration, because they are very urgent in institutions and institutions, because administration can lead and make such a big and strong contribution. Several reforms to Islamic boarding schools in terms of system and management issues can be used as an integral part of the improvement and development of madrasa educational institutions in the future. Keywords: management, madrasah management, Islamic education